Curcumin Attenuation of Wear Particle-Induced Osteolysis via RANKL Signaling Pathway Suppression in Mouse Calvarial Model - Cheng, Tao; Zhao, Yaochao; Li, Bin; Cheng, Mengqi; Wang, Jiaxing; Zhang, Xianlong (Mediators of Inflammation, 2017)
Wear particle-induced chronic inflammation and osteoclastogenesis are two critical factors in the osteolytic process. Curcumin (CUR) is an active compound of the medicinal herb Curcuma longa and has anti-inflammatory and antiosteoclastogenic properties. Our study tested the hypothesis that CUR might attenuate polymethylmethacrylate- (PMMA-) induced inflammatory osteolysis using mouse calvaria osteolysis model in vivo and in vitro. The mice were divided into four groups: phosphate-buffered saline group, CUR, PMMA, and PMMA + CUR groups. Three days before PMMA particle implantation, the mice were intraperitoneally injected with CUR (25 mg/kg/day). Ten days after the operation, the mouse calvaria was harvested for microcomputed tomography, histomorphometry, and molecular biology analysis. As expected, CUR markedly reduced the secretion of tumor necrosis factor-α, interleukin- (IL-) 1β, and IL-6 in the calvarial organ culture. Moreover, CUR suppressed osteoclastogenesis and decreased bone resorption in vivo compared with PMMA-stimulated calvaria. Furthermore, CUR downregulated the osteoclast-specific gene expression and reversed the receptor activator of nuclear factor kappa-B ligand (RANKL)/osteoprotegerin messenger RNA and protein ratio in PMMA particle-stimulated mice. These results suggest that CUR attenuated PMMA particle-induced inflammatory osteolysis by suppressing the RANKL signaling pathway in the murine calvarium, which could be a candidate compound to prevent and treat AL.